PROBIOTIC CHARACTERIZATION OF BACILLUS SUBTILIS STRAIN ISOLATED FROM INFANT FECAL MATTER REVEALED BY 16S rRNA GENE AND PHYLOGENETIC ANALYSIS - DAS, DEVARANJAN; RATH, CHANDI CHARAN; MOHANTY, NAKULANANDA; PANDA, SMITA HASINI (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The rationale of our study was to isolate and identify the putative probiotic strain from infant fecal matter exhibiting a broad range of antimicrobial activity and to analyze the effect of different culturing conditions on its probiotic properties and the production of antimicrobial metabolites. Methods: In the present study, bacterial strains were screened for probiotic properties and antimicrobial activity from infant fecal matter (6 months–2 years). The effect of varying culture conditions such as tolerance to acid, bile salt, phenol, NaCl, pH, incubation period, and temperature along with autoaggregation assay, hydrophobicity, and hemolysis was studied. The characterization of the potent strain was studied by morphological, biochemical, and 16S rRNA gene sequencing along the phylogenetic affiliation of the strain was studied. Results: Two putative probiotic bacteria (DAM and IFM) were isolated, identified, characterized, and predicted at pH 2.0, 3.0, and 4.0, the isolate IFM had 50%, 60%, and 70% survivability, while isolate DAM had 55%, 63%, and 75% survivability, respectively. At a bile salt concentration of 0.5%, both isolates had a 75% survival rate. The isolates exhibited a high percentage of hydrophobicity and autoaggregation. The isolates also had non-hemolytic activity and were susceptible to many clinical tested antibiotics (tetracycline, erythromycin, ampicillin, gentamycin, penicillin, etc.). The isolate showed antimicrobial activity against enteric pathogens such as Staphylococcus aureus, Escherichia coli, and Shigella dysenteriae. The accession number of Bacillus subtilis MT279753 and MK453362 was submitted to NCBI. Conclusion: The result revealed that isolates have potent probiotic properties and possess a direct influence on the production of antimicrobial metabolites. These parameters can be modified for the improvement of the potentiality of the isolates.